Early Imaging Prediction of Malignant Cerebellar Edema Development in Acute Ischemic Stroke. Issue 9 (September 2017) - Fabritius, Matthias P.; Thierfelder, Kolja M.; Meinel, Felix G.; Othman, Ahmed E.; Dorn, Franziska; Sabel, Bastian O.; Scheffler, Pierre; Ertl-Wagner, Birgit; Sommer, Wieland H.; Kunz, Wolfgang G.
Abstract : Background and Purpose—: Malignant cerebellar edema (MCE) is a life-threatening complication of acute ischemic stroke that requires timely diagnosis and management. Aim of this study was to identify imaging predictors in initial multiparametric computed tomography (CT), including whole-brain CT perfusion (WB-CTP). Methods—: We consecutively selected all subjects with cerebellar ischemic WB-CTP deficits and follow-up–confirmed cerebellar infarction from an initial cohort of 2635 patients who had undergone multiparametric CT because of suspected stroke. Follow-up imaging was assessed for the presence of MCE, measured using an established 10-point scale, of which scores ≥4 are considered malignant. Posterior circulation–Acute Stroke Prognosis Early CT Score (pc-ASPECTS) was determined to assess ischemic changes on noncontrast CT, CT angiography (CTA), and parametric WB-CTP maps (cerebellar blood flow [CBF]; cerebellar blood volume; mean transit time; time to drain). Fisher's exact tests, Mann–Whitney U tests, and receiver operating characteristics analyses were performed for statistical analyses. Results—: Out of a total of 51 patients who matched the inclusion criteria, 42 patients (82.4%) were categorized as MCE− and 9 (17.6%) as MCE+. MCE+ patients had larger CBF, cerebellar blood volume, mean transit time, and time to drain deficit volumes (all with P <0.001) and showed significantly lower median pc-ASPECTS assessed using WB-CTP (CBF, cerebellar blood volume, mean transit time, time to drain; all with P <0.001) compared with MCE− patients, while median pc-ASPECTS on noncontrast CT and CTA was not significantly different (both P >0.05). Receiver operating characteristics analyses yielded the largest area under the curve values for the prediction of MCE development for CBF (0.979) and cerebellar blood volume deficit volumes (0.956) and pc-ASPECTS on CBF (0.935), whereas pc-ASPECTS on noncontrast CT (0.648) and CTA (0.684) had less diagnostic value. The optimal cutoff value for CBF deficit volume was 22 mL, yielding 100% sensitivity and 90% specificity for MCE classification. Conclusions—: WB-CTP provides added diagnostic value for the early identification of patients at risk for MCE development in acute cerebellar stroke. Abstract : Supplemental Digital Content is available in the text.